Microbial Contamination of White Coats, Hands and Mobile Phones of Health Care Workers - Khan, Muhammed Irfan (International Journal of Pathology, 2020)
Background: Microbial contamination as the name suggests is the infiltration of pathogenic microbes into any living body. It increases the burden of disease and results in many fatal infections. The commonest reason behind microbial contamination in the health care system is health care workers. The risk of infections in tertiary care centers increases magnanimously despite a near-constant disinfection regimen being followed daily. Aside from the usual surfaces and equipment, infective agents are most commonly present on the hands of hospital staff, their mobile phones, and their clothing, specifically their lab coats.Objective: This study was planned to evaluate the microbial contamination of white coats, hands, and mobile phones of health care workers.Methods: This study, conducted in a tertiary care hospital in Karachi, estimates the percentage of microbial colonization on the white coats, mobile phones, and hands of health care workers. A total of 114 individuals were asked to obtain samples and a convenience sampling technique was used. Data were analyzed on SPSS version 17.0.Result: Lab coat contaminants were found to be Staphylococcus aureus (70%), Staphylococcus epidermidis (15.71%), and Escherichia coli (5.71%), Methicillin-Resistant Staphylococcus aureus MRSA (4.2%), Klebsiella (2.85%), and Pseudomonas (1.42%). The hands of observed health care workers mostly contained MRSA (32.32%) Staphylococcus aureus (29.29%), Staphylococcus epidermidis (29.29%), and Pseudomonas (9.09%). Mobile phones majorly held MRSA (37%), Staphylococcus epidermidis (36%), Staphylococcus aureus (21%), and Pseudomonas (6%).Conclusion: This cross-sectional study shows that a huge extent of health care worker’s apparel and belongings were tarnished with various types of microorganisms that can bring about nosocomial contaminations.